Mid-Cretaceous polar standstill of South America, motion of the Atlantic hotspots and the birth of the Andean cordillera - Somoza, Rubén (2008)
Fil: Somoza, Rubén. CONICET, Argentina. Departamento de Ciencias Geológicas, FCEyN, Universidad de Buenos Aires. Argentina.